Transformations in biblical literary traditions : incarnation, narrative, and ethics : essays in honor of David Lyle Jeffrey - Jeffrey, David Lyle, 1941-; Williams, Daniel H.; Donnelly, Phillip J. (Notre Dame studies in ethics and culture., 2014)
These essays not only acknowledge and clarify Jeffrey's achievement but also extend it in their attention to literary, philosophical, and religious works of the West.